Elucidation of blink reflex characteristics in Parkinson's disease subtypes through prepulse inhibition - Zhang, Zhen; Zhang, Ling; Huang, Xiaofeng; Hao, Xinqing; Li, Tao; Luo, Yayin; Yin, Xiaoxue; Song, Chunli; Liang, Zhanhua (Frontiers in Neurology, 2025)
This study investigated prepulse inhibition (PPI), a brainstem reflex, in Parkinson's disease (PD) patients. We compared PPI impairment between patients with postural instability and gait difficulty (PD-PIGD) and tremor-dominant (PD-TD) subtypes and explored potential lateralization effects. Fifty PD patients and 35 healthy controls underwent pre-pulse stimulation of the finger followed by stimulation of the supraorbital nerve. Compared to controls, PD patients exhibited impaired PPI across various stimulation intervals, with a more pronounced effect in the PD-PIGD subgroup. Interestingly, no significant differences in PPI were observed between the left and right sides, suggesting a bilateral effect. These findings suggest that abnormal brainstem circuits, potentially involving the pontine nucleus, contribute to PPI dysfunction in PD. Furthermore, the association between impaired PPI and the PD-PIGD subtype highlights a potential link with gait disturbances. Future research could explore the utility of PPI as a biomarker for gait dysfunction and treatment response in PD.